Electrorefining and electrodeposition for metal separation and purification from polymetallic concentrates after waste printed circuit board smelting. (1st March 2023) - Xia, Qinyi; Song, Qingming; Xu, Zhenming
Graphical abstract: Highlights: Electrorefining and electrodeposition treat polymetallic concentrates from WPCBs. Electrorefining shows well-adapted metal leaching and Cu upgrading functionalities. Cu 2+, Ni 2+, Fe 2+, and Zn 2+ sequential electrodeposition was evaluated. Complex electrochemical response mechanism of Ni 2+ to solution environment. Abstract: Multi metal recycling from waste printed circuit boards (WPCBs) is attractive for resource conservation and sustainability. While smelting is commonly adopted to produce polymetallic concentrates from WPCBs, current processes cost oxidation smelting and fire refining followed by electrorefining to deport co-existing base metals and recover copper, which can cause substantial metal losses, long steps, and lack of effective methods for subsequent base metal recycling. Here, direct electrorefining of polymetallic concentrates (Cu-Ni-Fe-Pb-sn-Au-Ag) combined with electrodeposition was investigated to realize multi metal separation and purification. It was found that direct electrorefining of concentrates in H2 SO4 /CuSO4 electrolyte at 0.4 V realized >98% base metal dissolution and copper production (∼99% purity), serving as a combined metal leaching and copper electrowinning procedure. PbSO4 -SnO2 -Cu5 FeS4 precipitate was formed in anode slime, with Ag-Au enriched by 8.5–61 times. Analysis on subsequent selective metal electrodeposition revealed the blocking effect of Zn 2+ and overlapped potential region of Fe 2+ -Ni 2+, emphasizing the importance of Zn and Fe pre-separation during smelting and chemical precipitation. Electrodeposition experiments demonstrated high selectivity for Cu and Ni at 0.05 and −0.7 V, where Ni 2+ shows complex electroreduction behaviors. The proposed process can serve as an alternative feasible route for multi metal recycling from WPCBs.